(untitled) (Journal of Parents and Teachers, 2025)
Just as we often say, ‘every mind is a world unto itself,’ this article may well lead us to say, ‘every school is a world unto itself.’ We come across the school career of Antonio, a young man who, at the age of 17, has attended seven different schools due to various circumstances. Born in Spain, he moved to New York at an early age, where he had the opportunity to attend several schools, from a Montessori-style school to some rather ‘dangerous’ ones, and finally to a magnificent and bright school, where it was easy to develop a love of reading. Then came the time to return to Spain, where at first he did not have a very good experience of camaraderie at school. Fortunately, a few years later, he found another school where he could find listening, dialogue and, above all, the experience of community.